2018
DOI: 10.1002/cncy.22066
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping salivary gland neoplasm of uncertain malignant potential based on cell type demonstrates differential risk of malignancy

Abstract: BACKGROUND The newly unveiled Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) has proposed salivary gland neoplasm of uncertain malignant potential (SUMP) as an indeterminate category. The category is reserved for fine‐needle aspiration (FNA) cases that are diagnostic of a salivary gland neoplasm but cannot be further designated as a specific tumor type. The objective of the current study was to evaluate the clinical utility of subtyping SUMP cases based on different cell types. METHODS A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 41 publications
2
54
4
Order By: Relevance
“…SUMP used in conjunction with a pattern‐based system may further refine the differential diagnosis, clarify which SUMP neoplasms show a greater ROM, and improve clinicians' understanding of MSRSGC in a clinically meaningful way. One study found statistically significant differences in the ROM among SUMP cases when they were subtyped as having an oncocytic/squamoid (61.1%), basaloid (40.0%), or myoepithelial morphology (18.8%) . In our cohort of basaloid SUMP cases, the ROM was 22%, which was much lower than that in the study by Hang et al In the pattern‐based risk‐stratification scheme, Griffith et al found that the category of basaloid neoplasm with nonfibrillary stroma had a much higher ROM (68.8%) than the category of basaloid neoplasm with fibrillary stroma.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…SUMP used in conjunction with a pattern‐based system may further refine the differential diagnosis, clarify which SUMP neoplasms show a greater ROM, and improve clinicians' understanding of MSRSGC in a clinically meaningful way. One study found statistically significant differences in the ROM among SUMP cases when they were subtyped as having an oncocytic/squamoid (61.1%), basaloid (40.0%), or myoepithelial morphology (18.8%) . In our cohort of basaloid SUMP cases, the ROM was 22%, which was much lower than that in the study by Hang et al In the pattern‐based risk‐stratification scheme, Griffith et al found that the category of basaloid neoplasm with nonfibrillary stroma had a much higher ROM (68.8%) than the category of basaloid neoplasm with fibrillary stroma.…”
Section: Discussioncontrasting
confidence: 67%
“…One study found statistically significant differences in the ROM among SUMP cases when they were subtyped as having an oncocytic/squamoid (61.1%), basaloid (40.0%), or myoepithelial morphology (18.8%) . In our cohort of basaloid SUMP cases, the ROM was 22%, which was much lower than that in the study by Hang et al In the pattern‐based risk‐stratification scheme, Griffith et al found that the category of basaloid neoplasm with nonfibrillary stroma had a much higher ROM (68.8%) than the category of basaloid neoplasm with fibrillary stroma. The findings of this study also support the importance of stromal character in that the ROMs of SUMP cases with fibrillary/chondromyxoid, hyaline, and absent stroma were 5.3%, 26.1%, and 37.5%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…Although this was lower than 35%, the value proposed by the MSRSGC, it was similar to the results in our study. Hang et al subclassified the neoplasms into basaloid, oncocytic/squamoid, and myoepithelial subtypes. The definition of the myoepithelial subtype does not correspond to the definition of the clear‐cell subcategory proposed by MSRSGC, which includes both the cytologic findings of classic pleomorphic adenoma with focal cellular atypia and those of tumors with predominantly myoepithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the uniform terminology allows cross communication between pathologists and institutions. Since the print publication of the MSRSGC in 2018, many institutions across the world retrospectively applied this tired diagnostic scheme to their institutional cohort of cases or those collected from multiple institutions and reported their findings with and without surgical follow‐up 6‐43 …”
Section: Introductionmentioning
confidence: 99%